The call of the unlived life: On the psychology of existential guilt - Binder, Per-Einar (Frontiers in Psychology, 2022)
This paper examines the psychology of existential guilt with Martin Heidegger and Rollo May's conceptualizations as the point of departure. The concept of existential guilt describes preconditions for responsibility and accountability in life choices and the relationship to the potential given in the life of a human. It might also be used as a point of departure to examine an individual's relationship to the potential offered in their life and life context and, in this way, the hitherto unlived life of an individual. The following questions are discussed in contexts of identity development, perfectionism, and current cultural shifts in conceptualizations of selfhood: How can humans relate to the fact that only limited parts of who they might be can ever be actualized? Moreover, how can they relate to the fundamental ambiguity and “groundlessness” in the contexts of life where choices are made? There are striking parallels between the role of exploration in the Eriksonian approaches to healthy identity development and the ontological groundlessness that stands out as a premise for existential guilt. There are also parallels between identity fore-closure and normative identity styles and “falling” into das Man in the existential framework. Perfectionistic ideals easily become an objectivization – and closure – of possible alternatives and choices. In contemporary theories of constructions of selfhood, the dangers of alienation from the community on the one hand and escape into what might become totalitarian collectivism on the other is pointed out. The contextualization of personal responsibility offered through the concept of existential guilt might address both dangers. It provides a perspective on how personal responsibility is embedded in contexts of human relationships, relationships to nature, and the finitude, freedom, uncertainties, and suffering that is given through human existence. Existential guilt can wake sorrow and regret over opportunities overlooked and lost. However, most of all, it can be seen as a drive toward repair in the relationship toward both oneself and the other. It takes the form of receptivity, an openness to a life not yet lived, and creative use of imagination.